Control of an over-actuated fixed-wing vectored thrust eVTOL - Enenakpogbe, Emmanuel; Whidborne, James F.; Lu, Linghai (Institute of Electrical and Electronics Engineers (IEEE), 2024)
A novel full-envelope controller for an over-actuated fixed-wing vectored thrust eVTOL aircraft is presented. It proposes a generic control architecture applicable to piloted, semi-automatic and fully-automated flight consisting of an aircraft-level controller (high-level controller) and a control allocation scheme. The aircraft-level controller consists of a main inner-loop non-linear dynamic inversion controller and an outer-loop proportional-integral linear controller. The inner-loop classical non-linear dynamic inversion controller is used for forward cruise flight while the outer-loop proportional-integral linear controller is used for hover/low speed control and position control. The control allocation scheme uses a novel architecture which transfers the non-linearity in the vectored thrust effector model formulation to the computation of the actuator limits by converting the effector model from polar to rectangular form thus allowing the use of a linear optimisation technique. The linear optimisation technique is an Active Set Linear Quadratic Programming constrained optimisation algorithm with a weighted least squares formulation. The control allocation allocates the overall control demand (virtual controls) to individual redundant effectors while performing control error minimisation, control channel prioritization and control effort minimization. Simulation results shows forward transition from hover to cruise and clearly demonstrates that the controller can handle saturation (position or rate). The proposed controller can also handle actuator failures.
Keywords: NDI; INDI; Transition; over-actuated; virtual controls; Full Envelope; easy-to-fly; effector model; VTOL; control allocation; Active Set; Weighted least squares; optimal; high level controller; unified control framework; real-time; online; constrained optimisation; linear quadratic programming